Nanoprecipitation for ultrafiltration membranes. Issue 9 (4th March 2015) - Wang, Qifeng; Samitsu, Sadaki; Fujii, Yoshihisa; Yoshikawa, Chiaki; Miyazaki, Toyohide; Banno, Hidekuni; Ichinose, Izumi
ABSTRACT: Polymer nanoparticles are readily obtainable by rapidly mixing a dilute polymer solution and a poor solvent. The nanoparticles of poly(vinylphenol), poly(vinylidene fluoride), and emeraldine base polyaniline prepared by nanoprecipitation become sticky when their diameters decrease down to a few tens of nanometers, and such polymer nanoparticles spontaneously assemble into rigid fractal networks of the nanoparticles. By filtering these fibrous nanoparticle networks on a microfiltration membrane, ultrafiltration membranes with a thin free‐standing filter cake layer made of nanoparticles are obtainable. The nanoparticle membranes are robust at least up to the applied pressure of 2 MPa and can separate 99% of 10 nm Au nanoparticles from the aqueous dispersion at the flux of more than 1835 L m −2 h −1 even at very low pressure difference of 0.08 MPa. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2015, 53, 615–620 Abstract : Rigid fractal networks of polymer nanoparticles several tens of nanometers in size are obtained through irreversible aggregation immediately following nanoprecipitation from dilute polymer solutions. These networks are useful as precursors for the fabrication of pressure‐resistant ultrafiltration membranes with a sharp cut‐off of less than 5 nm and an extremely high water flux.